Interatomic potential to study plasticity in stainless steels: The FeNiCr model alloy - Bonny, G. (2011)
Austenitic stainless steels are commonly used materials for in-core components of nuclear light water reactors. In service, such components are exposed to harsh conditions: intense neutron irradiation, mechanical and thermal stresses, and aggressive corrosion environment which all contribute to the components' degradation. For a better understanding of the prevailing mechanisms responsible for the materials degradation, large-scale atomistic simulations are desirable. In this framework we developed an embedded atom method type interatomic potential for the ternary FeNiCr system to model movement of dislocations and their interaction with radiation defects. Special attention has been drawn to the Fe-10Ni-20Cr alloy, whose properties were ensured to be close to those of 316L austenitic stainless steel. In particular, the stacking fault energy and elastic constants are well reproduced. The fcc phase for the Fe-10Ni-20Cr random alloy was proven to be stable in the temperature range 0-900 K and under shear strain up to 5%. For the same alloy the stable glide of screw dislocations and stability of Frank loops was confirmed.